(untitled) (Medico Legal Update, 2019)
This study aimed to investigate whether satisfaction with the quality of service and satisfaction with resident mediate the relationship between subjective health and depression. Toward this end, the following research questions were set. First, what is the correlation between satisfaction with the quality of service, satisfaction with resident, subjective health, and depression? Second, does satisfaction with the quality of service and satisfaction with resident mediate the relationship between subjective health and depression? The survey was conducted by visiting the nursing homes that allowed this study after a phone call request. Face-to-face interviews with the elderly people in the institutions were done by the investigator and trained graduate students. The survey was completed with 381 elderly people in long-term care facilities (Jan Feb 2017). The analysis of frequency, reliability, and correlation was done using the SPSS PC+ Win. 23.0programs. The mediation analysis and bootstrapping were done using the SPSS PROCESS macro program (model 6). This study found out that, in the effect of physical health on depression, satisfaction with the quality of service and satisfaction with resident have dual mediating effects. These findings were, first, the worse subjective health is, the higher depression is. Second, raising their satisfaction with the quality service provided by facilities can reduce their depression. Third, because satisfaction with resident can also reduce depression, it is necessary to lead the elderly to adjust themselves to the facilities, and to increase their residential satisfaction, which will reduce depression. First, by encouraging those in facilities to participate in various health programs and take care of their diets and by giving proper treatment, it is necessary to improve their health, which will reduce their depression. Second, by providing various environmental, physical, and social services which fit the demands of the elderly, it is possible to reduce their depression.